PERBEDAAN HASIL BELAJAR EKONOMI MENGGUNAKAN METODE PROBLEM SOLVING (PEMECAHAN MASALAH) DENGAN METODE CERAMAH PADA SISWA KELAS X IPS SMA N 3 TELADAN BUKITTINGGI - Eka Putri (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2018)
This research aims to know the difference between the results of learning economics students who are using the method of problem solving with method lectures. This research was carried out in SMA N 3 Teladan Bukittinggi. This type of research is a research quasi experiments with Pretest-Posttest Control Group Design. The population of this research is the whole grade X SMA N 3 Teladan Bukittinggi listed on the school year 2013/2014 as much as 407 students. The sampling method used purposive sampling method with the total sample of 64 students. X IPS 2 as an experiment, using the method of problem solving and X IPS 1 as the control class, use methods of the lecture. The type of the data being used is the primary data that (pre-test) and (post-test), then the data were analyzed by using the Z-test with α = 0.05. The results retrieved using the Z-test, Z-test analysis on post test retrieved Zhit = 2,19 and Ztab = 1.96 means Zhit Ztab >, then reject H0. So it can be inferred that the hypotheses there is a difference between the results of significant learning students who are taught using problem solving method and method lectures of class X students IPS SMA N 3 Teladan Bukittinggi. Where use of the problem solving method is better than on the method of lectures. It is recommended to teachers to consider methods of problem solving as an alternative in the learning process, particularly on the basis of competency describes the concept of management and applying the concept of management in school activities.